Interaction of Newly Synthesized Apolipoprotein B with Calnexin and Calreticulin Requires Glucose Trimming in the Endoplasmic Reticulum. Issue 3 (June 1999) - Tatu, Utpal; Helenius, Ari
Abstract : Apolipoprotein B (ApoB) is the only protein component of the low density lipoproteins (LDL) in plasma. It is a glycoprotein with a molecular mass of about 550 kDa (4536 amino acids) containing 16 N -glycans. We have studied the interaction of ApoB with two lectin-like chaperones of the Endoplasmic Reticulum (ER)'Calnexin (CN) and Calreticulin (CR). Using a co-immunoprecipitation approach we observed that newly synthesized ApoB associates with CN and CR. The interaction was transient; within 30–60 min after synthesis bulk of newly formed ApoB dissociated. Using McA Rh7777 cells expressing an N -terminal fragment of ApoB we found that inhibition of glucosidases in the ER prevented the association of CN and CR to newly synthesized ApoB. The results showed that like for association with other glycoprotein substrates, trimming of glucose residues was essential for ApoB binding to CN and CR.